Post-licensure safety of respiratory syncytial virus vaccines, Vaccine Adverse Event Reporting System, United States, May 2023–December 2024 - Junchao Li; Zhiyuan Zhang; Meixiang Wang (Preventive Medicine Reports)
Objective: Respiratory syncytial virus (RSV) vaccines, including Arexvy and Abrysvo, received approval in May 2023. The study aims to review the post-licensure safety of RSV vaccines by investigating adverse events using the Vaccine Adverse Event Reporting System (VAERS). Methods: We included VAERS reports of RSV vaccination in United States between May 3, 2023, and December 27, 2024. The study performed descriptive analysis, clinical review of death and pre-specified conditions, and data mining using empirical Bayesian methods. Results: VEARS received 6790 U.S. reports following administration of RSV vaccines. The median age of vaccine recipients was 71 years, with females comprising 64.9 %. Guillain-Barré syndrome (GBS) was the most common adverse event among serious reports. Injection site reaction was the most common non-serious report. 53 reports mention death, and the most frequent cause was sudden cardiac death. We identified 19 reports of anaphylaxis, 14 reports of cellulitis within 7 days of onset, and 81 reports of GBS. 63.2 % of vaccinees during pregnancy did not report adverse event, and the most common adverse event, was preterm delivery. Data mining displayed that various preferred terms were not identical based on vaccine and age stratification adverse event. Conclusions: The study reviewed the post-licensure safety of RSV vaccines and suggested that a significant proportion of adverse events were not serious, which aligned with previous studies. Preterm delivery and GBS following the administration of RSV vaccines require continuous monitoring. Additionally, inappropriate administration of Arexvy in pregnant individuals should be paid attention to.